The Impact of the Hybrid Education Model on Medical Students with Attention-Deficit/ Hyperactivity Disorder Symptoms During the COVID-19 Pandemic - Abdullah Yıldırım; Şakir Gıca; Erhan Kaya; Aybike Nur Sağır; Hayat Gaye Alkış (Neuropsychiatric Investigation)
Objective: The aim of this study is to evaluate the effects and outcomes of the hybrid education model, which became widespread during the pandemic period, on medical students with attention-deficit/hyperactivity disorder (ADHD) symptoms.